Cross-sectional survey to determine fatigue in patients with systemic lupus erythematosus - Lu, Jingya; Yu, Minmin; Xu, Rong (Frontiers in Psychology, 2024)
Background: Fatigue is a prevalent symptom among individuals with active systemic lupus erythematosus (SLE). We aimed to investigate the status quo and influencing factors of fatigue in patients with SLE, to provide insights to the clinical SLE treatment and care.Methods: We conducted a longitudinal survey on the fatigue of active SLE patients from June 2022 to November 2023 in our hospital. Fatigue severity scale (FSS), Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) were used for data collection. Pearson correlation and multiple stepwise regression analysis were conducted to analyze the relevant factors affecting the fatigue level of patients with SLE.Results: A total of 212 active SLE patients were included, the incidence of fatigue in active SLE patients was 55.66%. There were statistical differences in the fatigue score between SLE patients with different age and course of SLE (all P<0.05). Fatigue was positively correlated with anxiety (r = 0.559) and depression (r = 0.591) in patients with SLE (all P<0.05). Multiple stepwise regression analysis indicated that age, course of SLE, anxiety and depression were the influencing factors of fatigue in SLE patients (all P<0.05).Conclusions: Patients with SLE exhibit a significant degree of fatigue, which varies with respect to age, disease duration, and the presence of comorbid anxiety and depression. It is imperative that healthcare providers closely monitor the fatigue levels in this patient population and implement targeted interventions to mitigate the impact of fatigue on the quality of life and overall well-being of individuals with SLE.